RAC1 as a Novel Therapeutic Target for Acute Liver Failure. - Bueloni, Bárbara (2025)
Background & Aims: The Rho GTPase RAC1 regulates key processes in acute liver failure (ALF), including oxidative stress and inflammation. We aimed to evaluate the therapeutic potential of RAC1 pharmacological inhibition in ALF.Methods: Ingenuity Pathway Analysis and gene ontology analysis were performed on transcriptomic datasets from ALF patients (GSE38941 and GSE80751). ALF was induced in mice using Concanavalin A, acetaminophen, or D-Galactosamine/Lipopolysaccharide (n = 10-21/group). The RAC1 pharmacological inhibitor 1D-142 was used in vivo and in vitro. Hepatocytes and macrophages, from primary cultures and cell lines, were analyzed. RNA-Seq data from ALF mouse livers (n = 3/group) were correlated with human datasets. Human liver explants (n = 6) were treated in vitro with 1D-142.Results: RAC1 emerges as an upstream regulator in human ALF samples correlating with immuneactivation and oxidative stress responses (p<0.05). Administration of 1D-142 ameliorated liver injury in murine ALF models when administered at early or late stages post-injury (p<0.05). 1D-142 treatment diminishes reactive oxygen species formation (p<0.01), inflammatory cell migration (p<0.001), cytokine production (p<0.05) and hepatocytes death (p<0.05). Liver transcriptomics revealed that RAC1 inhibition modulates key dysregulated pathways in ALF. Human ALF liver explants treated with 1D-142 showed reduced necrosis (p<0.05) and reduced expression of pro-inflammatory genes (p<0.01).Conclusions: RAC1 drives sterile inflammation and oxidative stress in ALF, and its pharmacologicalinhibition protects in murine models, supporting its potential as a therapeutic target forthis condition. Impact and implications: Acute liver failure (ALF) is a life-threatening condition with limited treatment options and is characterized by severe inflammation and oxidative stress. Our study provides strong scientific justification for targeting the RAC1 protein, demonstrating that its pharmacological inhibition with 1D-142 reduces liver injury, immune cell infiltration, and oxidative damage in murine models of ALF and in human liver explants. These findings identify RAC1 as a novel therapeutic target and provide translational support for its potential clinical application in ALF.RAC1-targeted therapy merits further studies in clinical settings.